Stress and Coping Strategies among Nursing Students of selected Nursing College of Kathmandu - Amrita Dhakal; Muna Dhakal; Varsha Gurung (Journal of Karnali Academy of Health Sciences, 2025)
Background: As nursing students have to work in different wards and deal with different types of patients, the dynamic clinical and academic environment makes them continuously exposed to the stressful situations. The purpose of the study was to identify stress and coping strategies among nursing students of Kathmandu.